Assessment of industrial pollution and water quality index of Tunggak River at Gebeng Pahang, Malaysia - Mohammed Amjed, Hossain (2014)
Gebeng is an industrial estate that contained multifarious industries, which generate industrial effluents and consequently pollute the adjacent river water as well as surface water quality of the area. With the objectives to assess the water quality of the area with spatial and temporal variations, to classify the water based on water quality index, to assess the heavy metal contamination of soil due to the industrial pollution and to perform a water quality model to simulate the water quality parameters of Tunggak River, this study has been conducted. To fulfil the objectives, water and soil samples were collected and analysed. Water samples were collected for a period of one year from February 2012 to January 2013 from ten preselected sampling stations, and soil samples were collected from thirty sampling points according to the standard method of sample collection. Twenty-four water quality parameters including ten heavy metals and heavy metals in soil samples were analysed. The water quality model was calibrated and validated with the collected data. All testing and analyses were done in accordance with the standard method procedures. Data analysis was conducted using SPSS 16.0 statistical software. The results of water quality analyses showed that the concentrations of DO observed were very low (less than 4.0 mg/L) over the whole area, accordingly BOD (6.8 – 27.1 mg/L) and COD (14.0- 59.6 mg/L) were observed very high. Ammoniacal nitrogen and phosphorus were also recorded in higher concentrations. Compared to all areas the water qualities at the industrial zone were more deteriorated. According to the INWQS Malaysia recommended threshold levels, fifteen parameters were found to be beyond this level. The results from the calculation of the DOE-WQI revealed that the water of the Tunggak River was under class III and class IV and the swampy area was class III. According to the INWQS Malaysia, class IV water cannot be used for any purpose except irrigation. Soil heavy metal contamination investigation showed that five heavy metals were found contaminating the area that led to soil pollution. Soils of the industrial zone were polluted with arsenic, mercury, lead, cobalt and zinc. Arsenic and mercury contamination was observed all over the study area. Source apportionment study revealed that the major sources of pollution in both cases of water and soil were due to anthropogenic activities. The sources of physicochemical parameters were primarily of the industrial effluents associated with domestic wastewater, and agricultural and urban runoffs. Some parameters with heavy metals contamination were due to natural sources. The water quality model calibration and validation result showed that the model has represented the field data quite well. RMSE showed good match between the observed and simulated data. The model suggested that the lower concentration of DO could not be revived without taking proper management, including water quality control strategy. Several water quality control strategies were tested with the model to propose the best one for use to revive the water quality of the Tunggak River. It is proposed that the pollution load modification with 20.0 mg/L BOD + flow augmentation and imposing three weirs in critical locations- strategy would be able to control the minimum level of DO and maximum level of nitrogen and phosphorus of the Tunggak River. At the same time, it also recommended that the industries should be compelled to adhere strictly the Environmental Quality (Industrial Effluent) Regulations 2009, Malaysia before discharging BOD more than 20.0 mg/L and 6.0 kg/day into the Tunggak River.